Critical period for Italian ryegrass (Lolium perenne L. spp. multiflorum) control in winter wheat in North Carolina - Diego J. Contreras; Ramon G. Leon; Angela R. Post; Wesley J. Everman (Weed Technology)
Field studies were conducted in North Carolina to determine the critical period of weed control (CPWC) for Italian ryegrass in winter wheat. Soft red winter wheat was planted in late fall in 2017 and 2018 in no-till fields near Salisbury, NC. Treatments consisted of allowing weeds to grow from crop emergence for different intervals until removal (“weedy”), maintaining “weed-free” conditions from crop emergence for the same intervals, and then letting the weeds emerge and compete with the crop for the duration of the season. In 2017, weed removal occurred in 2-wk intervals from crop emergence up to 18 wk after crop emergence (WAE) and 3-wk intervals up to 18 WAE in 2018. Additional biological measurements, including Italian ryegrass density and height, were collected at 6, 12, and 18 WAE to characterize the effect of crop-weed interactions on the CPWC and weed populations. Nonlinear regression analysis was conducted to relate the timing of weed removal and yield loss. The analysis was carried out using growing degree days (GDDs) accumulated at corresponding WAE. Italian ryegrass density ranged from 292 to 824 plants m−2, which created intense competitive conditions with wheat. In the absence of weed control, yield loss surpassed 60%. Using 5% yield loss as an accepted threshold, the CPWC for Italian ryegrass in no-till planted wheat was estimated to be from 1,100 to 1,900 GDD. This relatively short period makes it possible to reduce weed control intensity if control actions are properly timed.